1991
DOI: 10.1128/mcb.11.5.2375
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6- and leukemia inhibitory factor-induced terminal differentiation of myeloid leukemia cells is blocked at an intermediate stage by constitutive c-myc.

Abstract: Interleukin-6 (IL-6) and leukemia inhibitory factor (LIF), two multifunctional cytokines, recently have been identified as physiological inducers of hematopoietic cell differentiation which also induce terminal differentiation and growth arrest of the myeloblastic leukemic M1 cell line. In this work, it is shown that c-myc exhibited a unique pattern of expression upon induction of M1 terminal differentiation by LIF or IL-6, with an early transient increase followed by a decrease to control levels by 12 h and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 42 publications
4
84
1
Order By: Relevance
“…13,14 In these cells induction by IL-6 or LIF resulted in the expression of certain differentiationrelated markers but the expression of late differentiation markers and growth arrest in the G 0 /G 1 phase of the cell cycle was prevented. These results are similar to our observation, in that induction by IL-6, GM-CSF, IL-4 or IFN-␥ alone led to a partial differentiation and a partial accumulation of the cells in G 0 /G 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 In these cells induction by IL-6 or LIF resulted in the expression of certain differentiationrelated markers but the expression of late differentiation markers and growth arrest in the G 0 /G 1 phase of the cell cycle was prevented. These results are similar to our observation, in that induction by IL-6, GM-CSF, IL-4 or IFN-␥ alone led to a partial differentiation and a partial accumulation of the cells in G 0 /G 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, erythroid differentiation was shown to be blocked by constitutive expression of c-myc in murine erythroleukemia (MEL) cells, [6][7][8] poietic and other cell lines. [9][10][11][12][13][14][15][16] Conversely, c-myc anti-sense oligonucleotides have been shown to induce differentiation of HL-60 and F9 cells. 17,11 c-Myc belongs to the basic/helix-loop-helix/leucine zipper (bHLHZip) family of transcription factors and requires heterodimerization with a partner, the bHLHZip protein Max, to exert its function.…”
Section: Introductionmentioning
confidence: 99%
“…Using the M1 cell line, this laboratory has shown that the protooncogenes c-myc and c-myb and the transcription factor E2F-1 are negative regulators, and Egr-1 is a positive regulator of terminal myeloid differentiation. [1][2][3][4][5] The early growth response gene 1 (egr-1), a macrophage differentiation primary response gene, has been shown to be essential for and to restrict differentiation along the macrophage lineage. 4 Ectopic Egr-1 expression potentiated macrophage differentiation of the hematopoietic precursor cell line 32Dcl3, and stimulated the development of bone-marrow-derived hematopoietic progenitor cells along the macrophage lineage at the expense of granulocyte and erythroid lineages.…”
Section: Introductionmentioning
confidence: 99%
“…The autonomously proliferating M1 myeloblastic leukemia cell line is induced by interleukin-6 (IL-6) to undergo terminal macrophage differentiation with concomitant loss of leukemogenicity, providing an attractive model system to analyse the different regulators of terminal differentiation. Using the M1 cell line, it has been shown in our laboratory that the proto-oncogenes c-myc and c-myb and the transcription factor E2F-1 are negative regulators, and Egr-1 is a positive regulator of myeloid differentiation (Nguyen et al, 1993;Hoffman-Liebermann and Liebermann, 1991;Selvakumaran et al, 1992;Krishnaraju et al, 1998;Amanullah et al, 2000).…”
Section: Introductionmentioning
confidence: 99%